A Study on Business Environment for Retailers on the Implementation of GST - Das, Daisy (AMC Indian Journal of Entrepreneurship, 2023)
Goods and service tax (GST) is a complete duty on services and goods having an esteem option at various stage with complete and a chain set of advantages from the producer to retailer. The objectives of this study were to determine the viability of GST in the Indian economy and determine benefits of retailers in implementing GST. The study was descriptive in nature and the researcher used convenient sampling technique. Primary data and secondary data were collected for the study. The study helped to know the impact of GST on retailers. The researcher found that retailers have poor knowledge about implementation and laws related to GST. The researcher suggested that government should take initiative to create awareness for retailers and regular updates should be made available to clients on GST related issues.